Fasting induces ANGPTL4 and reduces LPL activity in human adipose tissue - Philip M.M. Ruppert; Charlotte C.J.R. Michielsen; Eric J. Hazebroek; Ali Pirayesh; Gunilla Olivecrona; Lydia A. Afman; Sander Kersten (Elsevier, 2020)
Objective: Studies in mice have shown that the decrease in lipoprotein lipase (LPL) activity in adipose tissue upon fasting is mediated by induction of the inhibitor ANGPTL4. Here, we aimed to validate this concept in humans by determining the effect of a prolonged fast on ANGPTL4 and LPL gene and protein expression in human subcutaneous adipose tissue. Methods: Twenty-three volunteers ate a standardized meal at 18.00 h and fasted until 20.00 h the next day. Blood was drawn and periumbilical adipose tissue biopsies were collected 2 h and 26 h after the meal. Results: Consistent with previous mouse data, LPL activity in human adipose tissue was significantly decreased by fasting (−60%), concurrent with increased ANGPTL4 mRNA (+90%) and decreased ANGPTL8 mRNA (−94%). ANGPTL4 protein levels in adipose tissue were also significantly increased by fasting (+46%), whereas LPL mRNA and protein levels remained unchanged. In agreement with the adipose tissue data, plasma ANGPTL4 levels increased upon fasting (+100%), whereas plasma ANGPTL8 decreased (−79%). Insulin, levels of which significantly decreased upon fasting, downregulated ANGPTL4 mRNA and protein in primary human adipocytes. By contrast, cortisol, levels of which significantly increased upon fasting, upregulated ANGPTL4 mRNA and protein in primary human adipocytes as did fatty acids. Conclusion: ANGPTL4 levels in human adipose tissue are increased by fasting, likely via increased plasma cortisol and free fatty acids and decreased plasma insulin, resulting in decreased LPL activity.This clinical trial was registered with identifier NCT03757767.